Uji Aktivitas Antioksidan Pada Teh Chamomile Kemasan Berdasarkan Variasi Suhu Dan Lama Penyeduhan Dengan Metode Dpph (1,1-diphenyl-2-picrylhydrazyl) - Dhea Nur Fadhilah*; Binsar Sitorus; Tumpak Rudi Aman Manik; Eva Siburian (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
Antioxidants can neutralize free radicals and protect the body from various diseases by binding to free radicals and highly reactive molecules that can damage cells. Increased knowledge about free radical activity has resulted in the use of antioxidant compounds being increasingly developed for food, beverages, and treatment. Tea is a very popular drink and is consumed by almost all people in the world and become an important agricultural product, one of them is Chamomile tea. Chamomile tea comes from Chamomile flowers which contain lots of chemical compounds such as tannins and flavonoids namely: polyphenol compounds and their derivatives. Group of compounds Tea is one type of functional beverage because in tea is contained natural antioxidants, namely flavonoids that can keep the body from free radical attacks. This study aims to determine the influence of temperature and duration of brewing antioxidant power in the water of broom tea by using the DPPH method. This study used a randomized block design method (RAK), factor A is the brewing temperature (20˚C, 40˚C, and 50˚C) and factor B is the length of the brewing (2, 4, and 6 minutes) treatment combination of 9 treatments.The research results showed that with the higher temperature and duration of brewing the total content of the antioxidant power in tea steep also increased. And the combination of good performance based on the IC 50 test result is a combination of A3B3 (temperature brewing 50˚C for 6 minutes) with the highest total antioxidant equal to 232,4617 µg/mL sample. The result of a statistical test of Kurskal Wallis antioxidant activity of chamomile tea with a variation of temperature 20˚C, 40˚C, and 50˚C and brewing time 2 minutes, 4 minutes, 6 minutes there was a significant difference.